Temporal trends in cardiovascular disease risk factors attributed burden in Iran, 1990–2021 - Amir Hossein Behnoush; Sobhan Younesian; Seyede Maryam Mousavi; Shaghayegh Khanmohammadi; Ali Golestani; Mohammad-Mahdi Rashidi; Ozra Tabatabaei-Malazy; Nazila Rezaei; Mohsen Abbasi-Kangevari (Scientific Reports)
Abstract Evaluation of Cardiovascular diseases (CVDs), the leading cause of death worldwide, and their risk factors is critical for developing effective healthcare interventions, especially in developing countries like Iran, where economic and demographic challenges may impact healthcare outcomes. This study aimed to evaluate the temporal trends in the burden of CVDs risk factors Iran, a developing country in the Middle East, using the Global Burden of Disease (GBD) study 2021. The data from GBD 2021 was used for extraction, processing, and presentation of results. Deaths, disability-adjusted life years (DALYs), years of life lost (YLLs), and years lived with disability (YLDs) and attributable burden to all risk factors, in addition to metabolic, behavioral, and environmental/occupation risk factors were reported for Iran from 1990 to 2021. All burden metrics were reported as point estimates and 95% uncertainty intervals (UIs). From 1990 to 2021, the total number of deaths and DALYs attributed to CVDs risk factors increased by 99.28% (95% UI 85.93–112.36%) and 65.85% (55.88 to 77.01), respectively. However, the age-standardized rates of deaths and DALYs decreased significantly by 43.16% (− 46.34% to − 39.97%) and 45.82% (− 48.82 to − 42.71), respectively. Metabolic risk factors were the leading contributors to deaths and DALYs (189.98 [166.38 to 209.83] and 3575.8 [3206.1 to 3928.27], respectively), with high systolic blood pressure (SBP) accounting for the highest burden. Males, particularly in older age groups (≥ 80 years), experienced a higher burden compared to females. Although there was no clear relationship between Iran provinces’ sociodemographic index (SDI) and the burden of CVDs risk factors, regions with higher SDIs tend to have a lower burden of disease. Our findings indicate that while age-standardized burden rates have decreased, Iran still faces a significant burden of CVDs and associated risk factors. In this regard, high SBP needs special attention. These findings highlight the urgent need for subnational, risk-specific policies targeting high-risk populations and low-SDI provinces to reduce disparities and CVD burden. Immediate and targeted interventions are necessary to reduce disparities, lower healthcare costs, and address the high burden attributed to these risk factors.